A dialectical literary canon?. Issue 1 (2nd April 2020) - Toth, Hayley G.; Nicholls, Brendon
ABSTRACT: This article proposes a literary canon founded on dialectical principles, using South Africa as our historical example. In order to do so, we first trace the development of dialectical thought, moving from Georg Wilhelm Friedrich Hegel to Karl Marx to Steve Biko; from Eurocentrism to class consciousness to Black Consciousness. Second, we plot the influence of Hegel and Marx as well as Sartre and Fanon on Biko's elaboration of dialectics for the Black Consciousness Movement. Third, and in response to Marxist critiques of Black Consciousness, we register the moment of class consciousness that underpins Biko's politics, especially his critique of institutions. Finally, and based on our exposition of Biko's reading of Hegel via Marx and Sartre, we suggest a 'polythetic' dialectic to rework the post-Apartheid literary canon and to accommodate intersectional complexity within it. The canon, in our model, does not emerge from a settled consensus, but instead re-coalesces on every occasion that it is submitted to contestation or is approached via conflicts in the social. A transitive or dialectical canon might variously retain or negate institutionally-privileged texts while still making them momentarily visible via the 'popular' traditions of struggle that contest institutional privilege.